PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan Perbankan Tahun 2013 – 2017) - Dwi Mita Sari; Bambang Widarno; Djoko Kristianto (Universitas Slamet Riyadi, 2020)
This research examines the effect of Intellectual Capital toward financial performance. Variables that are used Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Capital Employed Efficiency (CEE) on Return on Assets (ROA) and Market to Book Value (MB). The populations in this research are all of banking companies listed on Indonesia Stock Exchange in 2013-2017. The populations in this research are 43 banking companies with 28 samples of banking companies. Technique of collection data uses purposive sampling. Technique of analysis data uses multiple regression, by carrying out the previoustesting with descriptive tests and clasic assumption tests. The result of this research shows that HCE,SCE, and CEE variable simultaneously has a significant effect on ROA and MB. Partially HCE, SCEand CEE have a positive effect and significant on ROA. Whereas HCE has a negative effect and notsignificant on MB, SCE has a positive effect and not significant on MB and CEE has a negative effectand significant on MB.